THE ROLE OF PAI TEACHERS IN INCREASING STUDENTS’ SPIRITUAL INTELLIGENCE OF MI MUHAMMADIYAH 1 PROBOLINGGO CITY - Gama Victorya Al Aziiz; Romelah; Dina Mardiana (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2024)
Abstract Teachers have an important role in education, especially in Islamic Education (PAI), where they encourage students to apply religious values in everyday life. This role is evident in their efforts to enhance students' spiritual intelligence, which aids them in facing life's challenges and improving their morality. This study aims to examine the role and steps taken by PAI teachers in improving the spiritual intelligence of students at MI Muhamadiyah 1 Probolinggo City. This study employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation involving the curriculum vice principal, PAI teachers, and students. The findings indicated that PAI teachers enhance spiritual intelligence through activities like congregational prayers, lectures, and the SQ program. Strategies such as the honesty canteen and the introduction of religious values help students understand the meaning of life and develop morals. The teachers help with worship practice and create a fun learning environment.